Engineering materials technology - Bolton, W. (William), 1933- (Newnes, 1993)
Engineering Materials Technology, Second Edition discusses the underlying principles of materials selection in mechanical and production engineering. The book is comprised of 20 chapters that are organized into five parts. The text first covers the structure of materials, such as metals, alloys, and non-metals. The second part deals with the properties of materials, which include fracture, fatigue, and creep. The third and fourth parts discuss the characteristics of metals and non-metals, respectively. The last part deals with the selection process; this part takes into consideration the vario.